2021
DOI: 10.51253/pafmj.v71i2.2966
|View full text |Cite
|
Sign up to set email alerts
|

Remission Rate of Pre-B All (Acute Lymphoblastic Leukemia) After Induction Chemotherapy Following United Kingdom Acute Lymphoblastic Leukaemia 2011 (Ukall 2011) Trial Protocol

Abstract: Objective: To find out the rate of remission of Pre-B Acute Lymphoblastic Leukaemia in children at the end of induction treatment with United Kingdom Acute Lymphoblastic Leukaemia (UKALL) 2011 chemotherapy protocol. Study Design: Prospective observational study. Place and Duration of Study: Paediatric Oncology Unit, Combined Military Hospital Rawalpindi, from Nov 2017 to Oct 2018. Methodology: Data of newly diagnosed patients of Pre-B Acute lymphoblastic Leukaemia, between 1 and 15 years of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
2
0
1
Order By: Relevance
“…Pendahuluan Leukemia Limfoblastik Akut (LLA) dikenal sebagai keganasan paling sering pada kelompok usia anak dan menyumbang 80% kasus leukemia akut dan subtipenya Pra-B LLA dianggap sebagai subtipe yang paling umum terjadi. 1,2 Salah satu terapi yang dilakukan untuk pengobatan LLA diantaranya adalah kemoterapi. Terdapat tiga fase pengobatan yaitu fase induksi, konsolidasi dan pemeliharaan, dimana pengobatan ini akan dilakukan secara bertahap.…”
Section: Aunclassified
“…Pendahuluan Leukemia Limfoblastik Akut (LLA) dikenal sebagai keganasan paling sering pada kelompok usia anak dan menyumbang 80% kasus leukemia akut dan subtipenya Pra-B LLA dianggap sebagai subtipe yang paling umum terjadi. 1,2 Salah satu terapi yang dilakukan untuk pengobatan LLA diantaranya adalah kemoterapi. Terdapat tiga fase pengobatan yaitu fase induksi, konsolidasi dan pemeliharaan, dimana pengobatan ini akan dilakukan secara bertahap.…”
Section: Aunclassified
“…In contrast, less marrow involvement indicated a lymphoma diagnosis. 9 various chemotherapeutic agents carried out sequentially during the induction, intensification and maintenance phases. 10 T-LBL and T-ALL are classified as NCI high-risk and treated with four drugs in induction, including vincristine, asparaginase, gluco-corticoids and anthracyclines.…”
Section: Introductionmentioning
confidence: 99%
“…Studies uniformly demonstrated improvement in an overall remission duration. 9 The proportional correlation of elevated white blood cell count and poor prognosis found in B-ALL is not strictly a feature of T-ALL. Therefore, allogenic bone marrow transplantation is left as the singular curative treatment for relapsed/refractory (R/R) patients.…”
Section: Introductionmentioning
confidence: 99%